Right Heart Catheterization on Sinus Venosus Type of Atrial Septal Defect with Partial Anomalous Pulmonary Vein Drainage - Pamrayogi Hutomo; Lucia Krisdinarti; Nahar Taufiq (ACI (Acta Cardiologia Indonesiana), 2016)
Atrial septal defect (ASD) is a non-cyanotic congenital heart disease characterized by the presence of defects on atrium septal wall. ASD is 10% of congenital heart disease. This defect is the third most common congenital heart disorder with an estimated incidence of 56 out of 100,000 live births. With the improved echocardiographic technique that can diagnose a defect in asymptomatic abnormalities, the estimated incidence is increased to 100 out of 100,000 live births. The disorder is more common in women than men with a ratio of male: female 1: 2.